The Involvement of Aquaporin-4 in the Interstitial Fluid Drainage Impairment Following Subarachnoid Hemorrhage - Liu, E.; Peng, Xianlong; Ma, Haowen; Zhang, Yan; Yang, Xiaomei; Zhang, Yixuan; Sun, Linlin; Yan, Junhao (Frontiers in Aging Neuroscience, 2021)
The mechanism of brain injury following subarachnoid hemorrhage (SAH) has not yet been clarified. The glymphatic system (GS), a glia-dependent waste clearance pathway, drains away soluble waste proteins and metabolic products, even some toxic factors from the brain. Aquaporin-4 (Aqp4) is highly expressed on the astrocyte foot processes and facilitates the interstitial fluid (ISF) transportation in the GS system. In this study, the role of Aqp4 in the GS injury after SAH was explored using Aqp4 gene knockout (Aqp4−/−) Sprague Dawley rats. The results of MRI, fluorescent imaging, and transmission electron microscopy (TEM) indicated that, after SAH, the inflow of cerebrospinal fluid (CSF) into the brain and the clearance of ISF from the brain were both significantly decreased. Meanwhile, the expression level of Aqp4 around the artery was markedly higher than that around the vein following SAH. Aqp4 knockout exacerbated the GS damage after SAH. In summary, after SAH, there was an apparent GS impairment, and Aqp4 played key roles in modulating the function of GS in the brain.